The Effect of Ginger Honey and Cocktail Honey Supplementation on Cortisol Levels in Balb/c Female Mice Induced Stress - Permatasari, Annisa Eka (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to investigate the effect of ginger honey and cocktail honey on decreasing cortisol hormone levels and to determine the difference in the effect of ginger honey (GH) and cocktail honey (CH) on decreasing cortisol hormone. This study is an in vivo study using the pre-test-post-test control group method. The sample used in this study were 25 Balb/c female mice which were divided into 5 groups (each group consist 5 mices); 1 control group and 4 intervention groups. The Intervention group divided based on different combination for ginger honey and different dose for cocktail honey; GH I (28 mg/20g BW/day), GH II (28 mg/20g BW/day), CH I (14 mg/20g BW/day) and CH II (28 mg/20g BW/day). All of group were given oral intervention using oral sonde for 14 days. Cortisol levels were examined using the ELISA method. Data were analyzed using statistical analysis T-test paired test. In this study it was found that the group of GH II given for 14 days could significantly reduce cortisol levels (p= 0.005, p <0.05) by -1,418 ng/ml and CH II can significantly reduce cortisol hormone levels (p = 0.005, p <0.05) by -0.806 ng/ml compared to the control group. However, among the two most influential on decreasing cortisol levels was GH II. This study concludes that the administration of ginger honey and cocktail honey can have an effect on reducing cortisol hormone levels and can be used as a supplement to deal with stress